2015
DOI: 10.1073/pnas.1509627112
|View full text |Cite
|
Sign up to set email alerts
|

CD31 signals confer immune privilege to the vascular endothelium

Abstract: Constitutive resistance to cell death induced by inflammatory stimuli activating the extrinsic pathway of apoptosis is a key feature of vascular endothelial cells (ECs). Although this property is central to the maintenance of the endothelial barrier during inflammation, the molecular mechanisms of EC protection from cell-extrinsic, proapoptotic stimuli have not been investigated. We show that the Ig-family member CD31, which is expressed by endothelial but not epithelial cells, is necessary to prevent EC death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 55 publications
(64 reference statements)
3
61
0
Order By: Relevance
“…1A). In line with this hypothesis, the authors showed that CD31 gene transfer was sufficient to recapitulate the cytoprotective mechanisms in CD31-negative pancreatic beta cells, which became resistant to T-cell-mediated rejection when grafted in fully allogeneic recipients (2).…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…1A). In line with this hypothesis, the authors showed that CD31 gene transfer was sufficient to recapitulate the cytoprotective mechanisms in CD31-negative pancreatic beta cells, which became resistant to T-cell-mediated rejection when grafted in fully allogeneic recipients (2).…”
mentioning
confidence: 82%
“…Akt activation by CD31 signaling in endothelial cells prevented the localization of the forkhead transcription factor FoxO3 to the nucleus, thus inhibiting the transcription of the proapoptotic genes and derepressing expression of the antiapoptotic gene cFlar (2). This study therefore provides important novel insights on the molecular mechanisms whereby the vascular endothelium remains undamaged while interacting with effector immune cells migrating to the site of the response.…”
mentioning
confidence: 88%
See 3 more Smart Citations